The Festive Play of Fernando Arrabal - Arata, Luis Oscar, 1950- (Book collections on Project MUSE., 2015)
Along with Samuel Beckett and Eugene Ionesco, Fernando Arrabal is a major exponent of the Theater of the Absurd. In this study Arrabal's plays are seen as a contemporary expression of a festive form of theater that flourished during the Middle Ages and that had its roots in the drama of Aeschylus and Aristophanes. With this view of Arrabal's work, Luis Arata explores the nature of play in art in the light of Jean Piaget's psychology. He thus offers a new way to approach festive and playful art.